Antiproliferative Activities of Dianella nemorosa Lam. Leaves Methanol Extract Against HCT-116, C2C12 and 293A Cell lines - Karim, Aditya Krishar; Asmara, Widya; Sismindari, .; Istriyati, .; Nohno, Tsutomu (Indonesian Research Gateway)
Dianella nemorosa Lam. (Liliaceae) is a medicinal plant traditionally used in Papua for treatment of cancer, injury, fracture, inflammation and also for antiseptic. The aim of this study was to evaluate antipriliferative activities of methanol extract of D. nemorosa leaves against HCT+116 (colorectal cell line), C2C12 (adherent mouse myoblast cell line) and 293A (Primary embryonal human kidney transformed with human adenovirus type 5 DNA). Powder of leaves was extracted using methanol. Antiproliverative activities were determined by cell proliferation reagents WST-1 assay for 1 h, 2h and 4h after 72h incubation. The result showed that methanol extract of D.nemorosa leaves showed remarkable antiproliferatiove activities against HTC-116 cell line with IC50 values of 199.31 μg/ml (1h), 197.87 μg/ml (2h) and 161.12 μg/ml (4h). The activities against C2C12 cell line resulted in the IC50 values of 405.51 μg/ml (1h), 435.12 μg/ml (2h) and 394.38 μg/ml (4h), while the IC50 values for 293A cell line were 580.81 μg/ml (1h), 442.21 μg/ml (2h) and 366.74 μg/ml (4h), respectively. Those results indicated that methanol extract of D.nemorosa leaves posses potential antiproliferative activities against HCT-116, C2C12 and 293A cell line. Further study is necessary to investigate the inhibitory mechanism of methanol extract of D. nemorosa leaves on HCT-116, C2C12 and 293A cell lines.Keywords : Dianella nemorosa Lam, cancer cell, HCT-116, C2C12, 293A